The Long March Toward Moral Leadership in Business - Rothlin, Stephan; McCann, Dennis P. (Silliman Journal, 2022)
This paper takes up the challenge in business ethics of how to achieve compliance with a firm’s or a profession’s or an industry’s code of ethics. Using the experiences that the authors have had in addressing this challenge, particularly in China, the paper attempts to map a solution beyond persuading institutions to adopt or adapt a code of ethics. While codes of ethics are necessary to achieve ethical integrity, they are not sufficient. What more is needed? The paper argues that a change of heart, informed by a convergence of the wisdom traditions represented by Confucian entrepreneurship and Catholic social teaching, provides a realistic basis for making progress toward moral leadership in business. The paper seeks to provide concrete practical guidance on how to walk the path toward its realization. While the argument is couched in terms that reflect the authors’ experiences in China, we believe that it is relevant to doing business, not only in China, but also in the Philippines and throughout East Asia and beyond.